Entrusting One’s Seal in the Ancient Near East in the First Half of the 2nd millennium BC - Patrier, Julie (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
It is an accepted fact that in the Ancient Near East, the seal was an eminently important object, one with several functions: a marker of identity, status and social differentiation (Patrier 2014 and Patrier forthcoming), an object with apotropaic value, a precious object, etc. (cf. overall Cassin 1987). However, some aspects of the actual use of the seal still remain unknown.